Geodiversidade funcional e os recursos hídricos superficiais e subterrâneos de Meridiano – SP - Xavier, Renata Lucon (2023)
With the growing demand for water supply and sanitation, it is crucial to adopt management plans to conserve the quality and quantity of surface and groundwater resources. In this context, this study aimed to map and quantify the functional geodiversity of Meridiano municipality, identifying environmental vulnerabilities such as erosive processes, dry springs, and degraded watercourses, as well as potential areas for aquifer recharge, to support local water resource management. Multiple sources of information were used, supplemented with field visits and integrated using QGis software. The geodiversity index (GI) was calculated by overlaying a 500 m x 500 m grid on thematic maps (drainage density, geology, pedology, and geomorphology) and tallying the elements in each cell. The GI ranged from 3 to 11, with high-ranking areas and hotspots concentrated in the São José dos Dourados River Basin due to greater diversity in rocks, soils, landforms, and major watercourses. Conversely, the Turvo/Grande River Basin, with lower drainage density, exhibited higher infiltration capacity, favoring aquifer recharge and availability of groundwater resources. Local geological formations consist predominantly of highly permeable and porous sandstones, contributing to the formation of permeable sandy soils, which help maintain aquifers and sustain rivers and streams during dry periods. Overlaying the land use and occupancy map with the geodiversity map revealed that citrus and sugarcane cultivation areas are in close proximity to numerous springs, indicating that unsustainable agricultural practices can contaminate and reduce the availability of these surface waters due to improper soil management and chemical use, posing a risk to groundwater as well. The methodology employed in this research proved effective in identifying the vulnerabilities and potentials of functional geodiversity concerning water resources, while the integrated mapping of information proved crucial for a comprehensive analysis. The results of this study have the potential to contribute to the field of geodiversity, particularly within the context of functional geodiversity, which is less explored in research. The classification of GIs provides valuable insights for the implementation of ecosystem management measures, especially in relation to water resources.